Calcium-binding protein, S100b, in the blood as a biochemical marker of the neurological state of men in warzones - Muraviova, D. V.; Buniatov, M. R.; UshakovаG. A. (Regulatory Mechanisms in Biosystems, 2018)
Acute and chronic stress are two of the most challenging issues faced by men situated in warzones. According to the main concept of G. Selye, stress response is the most important link during the adaptation of an organism to environmental factors. However, excessively intense or prolonged exposure to stress creates the threat of sustained homeostasis disorder. At present, the primary indicators in clinical studies are the general biochemical parameters of blood alanine aminotransferase, aspartate aminotransferase, bilirubin, creatine, urea, total protein, and glucose levels. But these indicators are not classical markers for determining the state of the nervous system itself and cannot reflect a patient’s mental state. In this regard, we tested for a different biomarker; we made an attempt to determine the neurospecific S100b protein in the blood serum by analyzing the correlation between classical and specific methods for diagnosing the state of the nervous system. For this study, blood was collected from 20 patients aged 25 to 45 years old. Participants were divided into two groups: one group of provisionally healthy men and another group of patients who were admitted to the Department of Neurology of the I. Mechnikov Regional Clinical Hospital after military operations (from the territory of the ATU). The standard test kits of PrAT Reagent Company (Dnipro) were used to assess biochemical indicators in accordance with the given instruction in the supplier’s protocol. The activity of each of alanine aminotransferase, aspartate aminotransferase, direct and total bilirubin content, creatine, urea, total protein levels, and astrocyte-specific protein S100b was examined. The level of alanine aminotransferase in the men from the warzone was 23.9 ± 3.9 μmol/l, compared with the healthy men 31.2 ± 0.7 μmol/l. The level of aspartate aminotransferase in the group of men at the neurological department was similar to that in the healthy group. The content of direct bilirubin in the patients at the neurological department increased by 28.0%, compared with the healthy men. The concentration of creatinine, total protein, urea, and glucose levels did not significantly change, compared with healthy volunteers and were in the range of the standard reference data. The content of astrocyte-specific protein, S100b, in the blood of the patients was 0.011 μg/ml, 36.0% more than in the conditionally healthy men 0.007 μg/ml. Prolonged stress could, therefore, induce profound changes in blood brain barrier and registration of neurospecific protein in the blood of men in warzones. These changes could become chronic if or when these men develop other social and economic problems that can be monitored with the specific marker for S100b.